Even apparently insignificant chemical deviations among bioequivalent generic antibiotics can lead to therapeutic nonequivalence: the case of meropenem (2014)
ABSTRACT: Several studies with animal models have demonstrated that bioequivalence of generic products of antibiotics like vancomycin, as currently defined, do not guarantee therapeutic equivalence. However, the amounts and characteristics of impurities and degradation products in these formulations do not violate the requirements of the U.S. Pharmacopeia (USP). Here, we provide experimental data with three generic products of meropenem that help in understanding how these apparently insignificant chemical differences affect the in vivo efficacy. Meropenem generics were compared with the innovator in vitro by microbiological assay, susceptibility testing, and liquid chromatography/mass spectrometry (LC/MS) analysis and in vivo with the neutropenic guinea pig soleus infection model (Pseudomonas aeruginosa) and the neutropenic mouse thigh (P. aeruginosa), brain (P. aeruginosa), and lung (Klebisella pneumoniae) infection models, adding the dihydropeptidase I (DHP-I) inhibitor cilastatin in different proportions to the carbapenem. We found that the concentration and potency of the active pharmaceutical ingredient, in vitro susceptibility testing, and mouse pharmacokinetics were identical for all products; however, two generics differed significantly from the innovator in the guinea pig and mouse models, while the third generic was therapeutically equivalent under all conditions. Trisodium adducts in a bioequivalent generic made it more susceptible to DHP-I hydrolysis and less stable at room temperature, explaining its therapeutic nonequivalence. We conclude that the therapeutic nonequivalence of generic products of meropenem is due to greater susceptibility to DHP-I hydrolysis. These failing generics are compliant with USP requirements and would remain undetectable under current regulations.